Using macroeconomic frameworks to analyze the impact of COVID-19 - Bulíř, Aleš,Baksa, Dániel,Corrales, Juan Sebastian,González, Andrés,Rodríguez, Diego,Heng, Dyna (International Monetary Fund, Institute for Capacity Development, 2021)
This technical note and manual (TNM) addresses the following issues: – Evaluating the full implications from the policies adopted to mitigate the impact of the COVID-19 pandemic on the economy requires a well-developed macroeconomic framework. This note illustrates how such frameworks were used to analyze Colombia and Cambodia's shock impact at the beginning of the pandemic. – The use of macroeconomic frameworks is not to infer general policy conclusions from abstract models or empirical analysis but to help policymakers think through and articulate coherent forecasts, scenarios, and policy responses. – The two country cases illustrate how to construct a baseline scenario consistent with a COVID-19 shock within structural macroeconomic models. The scenario is built gradually to incorporate the available information, the pandemic's full effects, and the policy responses. – The results demonstrate the value of combining close attention to the data, near-term forecasting, and model-based analyses to support coherent policies
10.5089/9781513571973.005
Keywords: Graue Literatur; Depositor preference; deposit insurance; bank; creditor hierarchy; Public Finance; Diseases: Contagious; Economic Theory; General Financial Markets: Government Policy and Regulation; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Bankruptcy; Liquidation; Health Behavior; Fiscal Policy; Debt; Debt Management; Sovereign Debt; National Government Expenditures and Related Policies: General; Aggregate Factor Income Distribution; Agriculture: Aggregate Supply and Demand Analysis; Prices; Macroeconomics; Public finance & taxation; Infectious & contagious diseases; Economic theory & philosophy; COVID-19; Public debt; Expenditure; Health; Supply shocks; Economic theory; Communicable diseases; Fiscal policy; Debts; Public; Expenditures; Public; Income; Supply and demand